METHOD OF SELECTION OF SUPPLIERS OF DIETARY SUPPLEMENT MANUFACTURING COMPANIES - Szentesi, Szabolcs; Tamás, Péter; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2021)
Literature analyzes show that there are a huge number of supplier selection methods in a wide variety of fields, however, there is little literature on medicine or dietary supplements. Among these publications, there is no developed method that would provide a general solution for the selection of a supplier of all food supplement companies. Some of the methods do not take into account quality parameters (eg. concentration, transport error rate, etc.) and others do not take into account aspects related to environmental protection, the importance of which is becoming more and more important nowadays. In the dissertation, a general decision-making method for the selection of suppliers of food supplement manufacturing companies is presented, which takes into account the logistical and environmental parameters in both qualitative and quantitative terms. The method presented in the dissertation is described through an example.